First record of Heterocucumis godeffroyi(Semper, 1868) (Echinodermata: Holothuroidea) from Peruvian sea - Solís-Marín, Francisco Alonso (2012)
This is the first record of Heterocucumis godeffroyi(Semper, 1868) (Echinodermata: Holothuroidea) for Peruvian waters. The species was collected at19 m deep, in Pucusana, off Lima Departamento. This record represents the northern most distribution limit knowing to the present. Reference material has been deposited at the Colección de Zoología Acuática, Laboratorio de Biología Marina, Departamento de Ciencias Biológicas y Fisiológicas, at Universidad Peruana Cayetano Heredia, Lima, Perú.